2022
DOI: 10.1186/s12893-022-01491-5
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel versus medial approach in laparoscopic radical right hemicolectomy for right colon cancer: a retrospective cohort study

Abstract: Purpose This study aimed to explore the feasibility and safety of the tunnel approach in laparoscopic radical right hemicolectomy for colon cancer. Methods From July 2016 to October 2018, a total of 106 consecutive patients with colon cancer who underwent laparoscopic radical right hemicolectomy at the Affiliated Cancer Hospital of Zhengzhou University were enrolled. The patients were stratified into either a tunnel approach (TA) (n = 56) group or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Currently, it is considered that factors related to the number of lymph nodes detected during colorectal cancer surgery, including tumor site size, length of surgical specimens, T-type classification, depth of invasion, and AJCC/UICC staging. They are predictive factors of the number of lymph nodes in colorectal cancer surgery [ 8 , 10 , 19 ]. However, several studies have indicated that the surgical approach is not correlated with the number of lymph nodes detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is considered that factors related to the number of lymph nodes detected during colorectal cancer surgery, including tumor site size, length of surgical specimens, T-type classification, depth of invasion, and AJCC/UICC staging. They are predictive factors of the number of lymph nodes in colorectal cancer surgery [ 8 , 10 , 19 ]. However, several studies have indicated that the surgical approach is not correlated with the number of lymph nodes detected.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that the middle approach is a safe and effective way to achieve CME and D3 lymph node dissection currently [ 7 ]. However, the operation takes a long time, and it is easy to cause more intraoperative bleeding [ 8 ]. In recent years, with the development of surgical technology, surgical approaches have been continuously optimized.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, laparoscopic right hemicolectomy with CME is widely accepted for colon cancer. However, owing to the complexity of laparoscopic right hemicolectomy, difficult cases have a notable incidence of intraoperative complications (18.0%) and of conversion from laparoscopy to the open approach (6%) 4 . Although conversion and intraoperative complications should not be considered surgical failures, these factors influence the postoperative recovery.…”
Section: Introductionmentioning
confidence: 99%